Revocation of Political Rights of Corruptors from a Human Rights Perspective in the Indonesian Legal System - Nur Arba Asari; Ramsul Nababab; Windawati Pinem; Arief Wahyudi; Sri Hadiningrum (Jurnal Kewarganegaraan, 2026)
This study aims to examine how the additional sanction of revocation of political rights for convicted corruptors is applied in court. A person declared a convicted corruptor faces an additional sanction in the form of revocation of political rights to hold public office. The research method in this study is normative juridical, which aims to analyze legal regulations. This type of research is analytical, descriptive legal research, which aims to systematically describe the legal facts, legal regulations, and legal implementation related to the revocation of political rights from a human rights perspective in the Indonesian legal system. The results of this study indicate that the application of revocation of political rights for corruptors in court is not evenly distributed in all corruption cases. One contributing factor is the judge's consideration in maintaining the existence of human rights. In addition, this study found that the revocation of political rights for corruptors has a clear legal basis, but its application is not yet consistent, so clear guidelines regarding legal regulations are needed.